POLITICAL PARTICIPATION: FROM ANTIQUITY TO THE PRESENT - Batalov, Oleksii; Semyboroda, Kateryna (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2024)
This study has explored the historical evolution of citizens’ political participation: from direct democracy in ancient city-states to modern digital mechanisms of civic engagement. It has examined the factors that influenced the transformation of citizen involvement in the political process, including: the direct participation of adult male citizens in the politics of ancient city-states, feudal monarchies in medieval Europe, the development of Enlightenment ideas and the formation of nation-states in the 18th–19th centuries, and the impact of globalization and digital technologies (including social media and e-governance) in the late 20th and early 21st centuries. Various forms of political participation have been analyzed, encompassing both traditional methods (elections, referendums, party activity) and modern digital tools of political engagement (online platforms, electronic petitions, political activity on social media, digital voting). The study has examined the impact of digitalization on political processes in the contemporary world and concluded that modern digital technologies, on the one hand, offer new opportunities for democracies (up to the revival of ancient direct democracy on virtual agoras (public platforms)), while on the other hand, they provide non-democratic regimes with powerful tools for spreading propaganda (both domestically and abroad) and maintaining control over their own populations. The study has analyzed the challenges associated with the use of emerging technologies in political life, particularly the risks of manipulation and disinformation, hacker attacks, and the digital divide. Special attention has been given to the analysis of risks linked to the use of modern digital platforms in political processes: manipulation of public opinion, fake news, and the issue of cybersecurity. The role of e-governance in engaging citizens in public administration has been explored, along with the function of social media as a platform for political mobilization and online activism as a new form of civic initiative. It has been concluded that the future prospects of political participation will depend on how effectively societies and state institutions can adapt to new technologies and ensure citizen engagement at all levels of political life. The main mechanisms for protecting the information space have been outlined in order to maximize the benefits of digital technologies.